A diferença entre o corpo do menino e da menina e seus cuidados - Verão, Silvana Pedrosa; Bernardo, Lucia Valério da Silva; Silva, Rosicler Gonçalves da; Carraro, Márcia Regina Simpione (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
VER PDF